2008
DOI: 10.1007/s11664-008-0448-x
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Tellurium Enrichment on CdZnTe Crystal Surfaces Detected by Raman Spectroscopy

Abstract: Synthetic CdZnTe or "CZT" crystals can be grown under controlled conditions to produce high quality crystals to be used as room temperature radiation detectors. Even the best crystal growth methods result in defects, such as tellurium secondary phases, that affect the crystal's performance. In this study, CZT crystals were analyzed by micro Raman spectroscopy. The growth of Te rich areas on the surface was induced by low powered lasers. The growth was observed versus time with low power Raman scattering and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
5
27
1
Order By: Relevance
“…Topographic images show that these areas of increased conductivity correspond to a pile-up of material that occurs on the edges of the laser damaged areas-consistent with a combination of both of the aforementioned hypotheses that (1) Cd material is being evaporated from the surface and (2) free Te atoms are migrating to these heated areas. These data, in combination with previous Raman results, 16 suggest that the increased conductivity is a result of a localized increase in Te in the areas exposed to the laser. We also note that the difference in conductivity between the Te rich laser damaged areas and the surrounding bulk is an order of magnitude smaller than that of similar C-AFM studies of surfaceterminated Te rich SPs.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Topographic images show that these areas of increased conductivity correspond to a pile-up of material that occurs on the edges of the laser damaged areas-consistent with a combination of both of the aforementioned hypotheses that (1) Cd material is being evaporated from the surface and (2) free Te atoms are migrating to these heated areas. These data, in combination with previous Raman results, 16 suggest that the increased conductivity is a result of a localized increase in Te in the areas exposed to the laser. We also note that the difference in conductivity between the Te rich laser damaged areas and the surrounding bulk is an order of magnitude smaller than that of similar C-AFM studies of surfaceterminated Te rich SPs.…”
supporting
confidence: 84%
“…Using the Raman laser, a series of highly damaged fiducial marks (~20 mW) were created as well as a series of lower laser power exposure areas (~160 mW to 1.7 mW) for subsequent AFM evaluation (see Figure 2). Raman spectra were collected simultaneously with the surface laser exposure with a 100X objective and a cooled charge-coupled device (CCD) camera detector.The Raman spectra of the untreated, freshly polished surface are consistent with those reported previously, 16 and were collected with lower laser power (less than 100 µW) in order to reduce the damage to the crystal.The surface of CZT3-7-8 was also exposed to a Raman laser (632.8 nm, HeNe) in four different regions for ~30 seconds (s) each. Previous studies of this crystal showed that while it has a high concentration of SPs within the crystal, the detector performance was not adversely influenced.…”
supporting
confidence: 73%
See 3 more Smart Citations